EFFECT OF PROFITABILITY , LIQUIDITY, FREE CASH FLOW , AND COMPANY SIZE TO COMPANY VALUE WITH STRUCTURE CAPITALAS INTERVENING VARIABLES ON MINING COMPANIES LISTED INSTOCK EXCHANGE INDONESIA - Fitri, Melvi; Erlina, Erlina; Situmeang, Chandra (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to examine and analyze the effect of Profitability, Liquidity, Free cash flow, and firm size on Firm Value through Capital Structure as an intervening variable in mining companies listed on the Indonesia Stock Exchange. The population of this study is all mining companies listed on the Indonesia Stock Exchange for the period 2014-2020. The sample used in this study amounted to 30 companies. This type of research uses associative research methods. Data analysis used path analysis approach using SPSS program. The results showed that profitability had a positive and significant effect on firm value. Liquidity, free cash flow , firm size, and capital structure have a negative and insignificant effect on firm value. Profitability and liquidity have a negative and significant effect on capital structure. Free cash flow has a positive and insignificant effect on the capital structure. Firm size has a positive and significant effect on capital structure. Based on the results of the mediation test, it shows that the Capital Structure is not able to act as an intervening variable.